Civil Servants in New Uzbekistan Mechanisms for the Development of Professional Culture - Yorkinoy Ernazarova (Researchparks Publishing, 2023)
The tasks aimed at improving the public administration system of any government directly depend on the modern needs of society for quality public services. In the course of reforms carried out to improve the public administration system in our country, improving the professional skills and culture of civil servants working on the basis of the principles of law, justice and humanity, in any case, was defined as the conceptual basis. This article dedicates the mechanisms of development of the professional culture of civil servants in New Uzbekistan.